Revisiting the Anti-Drug Antibody Assay Drug Tolerance of a Commercial Biological Product - James Zanghi; Nancy Yu; Benjamin T. Andrews; Phyllis Chan; Maxime Usdin; Cecilia Chiu; WeiYu Lin; Alyse Lin; Yuan Song (The AAPS Journal, 2025)
Drug tolerance (DT) is a critical attribute of anti-drug antibody (ADA) assays for assessing clinical immunogenicity. We present a unique situation where a previously approved commercial product, atezolizumab, required re-assessment of the assay DT to meet an increased drug exposure demand arising from a new route of administration (subcutaneous) and align with updated health authority (HA) regulations. Rather than redevelop the existing ADA assay, which could disrupt ongoing clinical trials, we identified a new anti-idiotype (anti-ID) antibody surrogate that demonstrated that the assay maintained adequate DT for the new route of administration. This streamlined approach addressed concerns regarding higher serum trough concentrations with subcutaneous administration and stricter sensitivity expectations. We established a target DT concentration based on population pharmacokinetic modeling to ensure adequate ADA characterization at steady state. This case study highlights the value of having alternative surrogate ADAs and demonstrates that achieving stringent DT requirements can be accomplished without extensive method redevelopment. We also introduce the broader implications of surrogate ADA selection, binding kinetics, and the clinical relevance of achieving high DT in the context of atezolizumab's efficacy and safety profile. This work also emphasizes the importance of considering bioanalytical assay characteristics, such as DT, throughout a product’s lifecycle. Graphical Abstract